2021
DOI: 10.3390/agronomy11050913
|View full text |Cite
|
Sign up to set email alerts
|

Physio-Anatomical Study of Polyploid Watermelon Grafted by Different Methods

Abstract: Watermelon is one of the most desirable vegetable crops in the world. Recently, grafting is common in watermelons worldwide, but not all grafting methods are compatible with polyploids. In this study, diploid, triploid, and tetraploid from one watermelon variety, “Mi Mei”, were grafted on the “Xijiaqiangsheng” squash rootstock to study the effect of genome duplication on graft compatibility. Three grafting methods (splice, hole, and tongue) were used to determine graft compatibility. Significant differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Other studies indicate new cambium derived from the callus tissue is formed across the graft interface, and several phloem and xylem connections that cross the graft interface are crucial for the successful and complete graft union (Fernández-García et al, 2004;Trinchera et al, 2013). Further, compatible grafting combinations with watermelon scion appear to have a longer adhesion region (the area of callus formation between the scion and rootstock) than incompatible combinations at 15 DAG (Kaseb et al, 2021). In another study, morphological changes occurred earlier on the scion side than on the rootstock side in graft unions between cucumber (C. sativus 'Zhongnong NO.26') on pumpkin rootstock (C. moschata 'Jingyan NO.5') using the hole-insertion, tongue-insertion, or splice-grafting with one-cotyledon methods.…”
Section: Resultsmentioning
confidence: 96%
“…Other studies indicate new cambium derived from the callus tissue is formed across the graft interface, and several phloem and xylem connections that cross the graft interface are crucial for the successful and complete graft union (Fernández-García et al, 2004;Trinchera et al, 2013). Further, compatible grafting combinations with watermelon scion appear to have a longer adhesion region (the area of callus formation between the scion and rootstock) than incompatible combinations at 15 DAG (Kaseb et al, 2021). In another study, morphological changes occurred earlier on the scion side than on the rootstock side in graft unions between cucumber (C. sativus 'Zhongnong NO.26') on pumpkin rootstock (C. moschata 'Jingyan NO.5') using the hole-insertion, tongue-insertion, or splice-grafting with one-cotyledon methods.…”
Section: Resultsmentioning
confidence: 96%
“…The grafting process was performed after 15 and 20 days after rootstock seeds sowing. The splice grafting method was used 31 , 49 (Fig. S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pina et al 18 found that reduced auxin and lignification, which are associated with high phenols in incompatible grafts, could indicate weak graft junctions, reactive oxygen species (ROS) 19 22 , or hormone imbalance 11 , 23 , 24 . IAA and cytokinin play vital roles in regulating rootstock/scion interactions 25 , and are necessary for vascular bundle regeneration at the graft union 26 , 27 , the differentiation of vascular tissues and wound healing 21 , 22 , 28 31 . There are three main classes of auxin-responsive genes: the GH3, Aux/IAA, and SAUR gene families 32 35 .…”
Section: Introductionmentioning
confidence: 99%